Anatomical variations of the frontal sinus drainage pathway according to the IFAC classification: frequency and interobserver agreement in a Paraguayan population (European Journal of Health Research, 2026)
Objective: To determine the frequency of anatomical variations of the frontal sinus drainage pathway (FSDP) according to the International Frontal Sinus Anatomy Classification (IFAC) and to assess interobserver agreement in a Paraguayan population.Methods: An observational, descriptive, analytical, cross-sectional study was conducted in 203 patients (406 FSDPs) with paranasal sinus computed tomography. Two otolaryngologists independently classified frontal-ethmoidal cells following the IFAC system. Frequencies, 95 % confidence intervals (CI95 %), and interobserver agreement were analyzed using Cohen’s κ, PABAK, and Gwet’s AC1, with clustering adjustment for paired sides per patient.Results: Mean age was 37.3 ± 16.3 years; 54.7 % were female. The most frequent cells were agger nasi (95.1 %), suprabullar (85.2 %), and supra-agger nasi (50.3 %). Less frequent variants included frontal suprabullar (18.7 %) and frontal supra-agger nasi (17.5 %). No significant differences were found by sex, age group, or laterality (p > 0.05). Overall interobserver agreement was moderate-to-good (κ = 0.693; 95 % CI 0.64–0.74), with high consistency confirmed by PABAK (0.74) and Gwet’s AC1 (0.77).Conclusion: The most frequently identified anatomical variations of the frontal sinus drainage pathway according to the IFAC classification were the agger nasi cell (95.1%), the suprabullar cell (85.2%), and the supra-agger nasi cell (50.3%). Application of the IFAC classification demonstrated moderate to good interobserver agreement (κ = 0.693), confirmed by the PABAK and AC1 indices, supporting its reproducibility and usefulness for anatomical assessment of the frontal recess in clinical practice and endoscopic surgical planning.
Keywords: Anatomy; Frontal sinus; Tomography, X-Ray Computed; Paranasal sinuses; Anatomic variation; Interobserver agreement